Who Did the Iconoclasm in the Dura Synagogue? - Kelley, Christopher Pierce (Bulletin of ASOR, 1994)
The question of who gouged eyes on the biblical murals of the third century Dura synagogue has not previously been settled. Kraeling stated without explanation that the iconoclasm was done by those (Roman soldiers) filling the synagogue with earth in preparation for the siege of 256-57. Goodenough argued that it was done by Jews who disapproved of the paintings as a violation of the second commandment. Close review of the evidence reveals a pattern of damage consistent only with Kraeling's intuition: It was done by a Roman, not by Jews.